The causal relationship between immune cell phenotypes and esophageal cancer development: a bidirectional Mendelian randomization study - Xun Zhang; Hailang Zhou; Qianqian Meng; Weiyi Wang; Lu Zhou; Ying Xu; Haiqin Zhang; Zixu Zhang; Jinnian Cheng; Xiaopeng Zhan; Ji Li; Changping Hu; et al. (Discover Oncology)
Abstract Background Immune cell phenotypes have been implicated in the development and progression of esophageal cancer (EC), but their causal relationships remain unclear. This study aimed to explore the potential causal associations between immune cell traits and EC risk using Mendelian randomization (MR) analysis. Methods A bidirectional two-sample MR analysis was conducted using genome-wide association study data from European populations. Genetic variants significantly associated with 731 immune cell phenotypes (P < 5 × 10−8) were selected as instrumental variables. The primary analysis employed the inverse variance weighted method, with sensitivity analyses including MR-Egger, weighted median, simple mode, and weighted mode methods. Heterogeneity and pleiotropy were assessed using Cochran’s Q test and MR-Egger intercept test. Results Seven immune cell phenotypes were positively associated with an increased risk of EC, including SSC-A + on CD8 + T cells (P = 0.006), CD16 + monocytes (P = 0.013), and myeloid dendritic cells (P = 0.014). Conversely, CD3 + on HLA-DR + T cells (P = 0.017) and CD4 + T cell absolute count (P = 0.014) showed protective effects against EC. Sensitivity analyses confirmed these associations with minimal heterogeneity or pleiotropy. Reverse MR analysis found no evidence suggesting that EC causally influences immune cell phenotypes. Conclusion This study provides genetic evidence supporting causal relationships between specific immune cell phenotypes and EC risk. Immune traits such as T cells, monocytes, and dendritic cells may serve as potential biomarkers or therapeutic targets for EC management. Further studies are needed to validate these findings and explore their clinical implications.